THE IMPLEMENTATION OF THE FAMILY HOPE PROGRAM (PHK) IN BINJAI HULU DISTRICT, SINTANG REGENCY - Mathilda Sunta; Yulius Yohanes; Arifin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This research aims to analyze and describe the implementation of the Family Hope Program (Program Keluarga Harapan or PKH) in Binjai Hulu District, Sintang Regency. The results indicate that Communication in the planning and decision-making process regarding the fuel subsidy reduction compensation program was conducted by the government using a "top-down" approach; consequently, the target community was not given the opportunity to provide input regarding their actual needs based on real-world conditions. Regarding Resources, the direct cash assistance lacked clarity in both its short-term and long-term objectives. The Disposition/Attitude of Implementers in the success of data collection for poor households, the distribution of fuel compensation cards (BLT), and the disbursement of direct cash assistance funds in Binjai Hulu District was rated as very good. Finally, the Bureaucratic Structure in the PKH fund distribution program carried out by the Post Office was considered appropriate, as the Post Office is highly experienced in handling public fund transfers and has a presence in nearly every district.